PREPARING A CORPORATE SOCIAL RESPONSIBILITY (CSR) DISTRIBUTION STRATEGY TO CREATE GROUP INDEPENDENCE IN PT PLN (PERSERO) PARENT UNIT IN THE NORTH SUMATRA REGION - Benny Candra Kurniawan; Nazaruddin; Iskandarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Corporate Social Responsibility (CSR) is a commitment to improving community welfare through free business practices and contribution of company resources. However, the funds provided only created dependency and some businesses were even forced to close because they were unable to be independent. The Asset Based Community Development method is in line with the CSR spirit to improve community welfare. Therefore, the stages carried out in the research are collecting asset data, determining targets, developing asset-based strategies, determining the duties and responsibilities of each actor, and preparing steps to achieve the strategy that has been prepared. In this way, eight strategies were obtained which aimed at community independence and increasing the income of community members.